2018
DOI: 10.1002/btpr.2709
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feed quality due to clarification strategy on the design and performance of protein A periodic counter‐current chromatography

Abstract: The impact of two different quality feeds, derived using two different harvest clarification processes, on protein A periodic counter‐current chromatography (PCC) design and performance is investigated. Data from batch experiments were input into a model to design optimal PCC operating parameters specific to each feed material. The two clarification methods were: depth filtration using a wetlaid matrix which has Q‐functionality; and a combination of depth filtration and chromatographic clarification, using a Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…For protein A chromatography, a silica-based resin (Prosep Ultra Plus, Millipore, Hertfordshire, UK) was used. The model protein for this study was IgG1, protein A purified humanised IgG1 produced in CHO cell culture, as described in El-Sabbahy et al, [19]. It was dialysed into a running buffer (sodium phosphate, pH 7.2) with a final concentration of 1 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…For protein A chromatography, a silica-based resin (Prosep Ultra Plus, Millipore, Hertfordshire, UK) was used. The model protein for this study was IgG1, protein A purified humanised IgG1 produced in CHO cell culture, as described in El-Sabbahy et al, [19]. It was dialysed into a running buffer (sodium phosphate, pH 7.2) with a final concentration of 1 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…This approach can reduce DNA complexes in harvest CCF down to <100 ppb levels (Koehler, Jokondo, Narayan, Voloshin, & Castro‐Forero, 2019). Numerous previous studies have demonstrated strongly reduced HCP impurity levels in the Protein A elution pool, compared to traditional depth filters (Castro‐Forero, Jokondo, Voloshin, & Hester, 2015; El‐Sabbahy et al, 2018; Gilgunn et al, 2019; Singh et al, 2017). One of these studies also demonstrated removal of histone proteins to below the detection limit (Gilgunn et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…The impact of two different quality feeds (one from depth filtration and other from a combination of depth filtration and chromatographic clarification) on Protein A PCC was studied, with the result that there was 49% increased productivity for the chromatographically clarified material over 100 cycles, with 11-fold lower HCP and a 4.4 LRV for HCDNA (El-Sabbahy et al, 2018). Upscaling of Protein A continuous chromatography using the Cadence TM BioSMB PD and the Cadence TM BioSMB Process 80 system was successfully carried out for a 10-day run time using feed from a perfusion culture and resulted in a 400-500% increase in vs. batch mode (Ötes et al, 2018).…”
Section: Continuous Chromatographymentioning
confidence: 99%